Oral Health and Patterns of Dental Visits Among Diabetic Patients in the Eastern Province of Saudi Arabia - AlTuraiki AM; Jaemal HM; Alamer AA; Alghwainem AA; Althabit TA; Alamri A; Nazir MA (Dove Medical Press, 2021)
Ahmad Mohammed AlTuraiki,1 Hamed Mohammed Jaemal,1 Ali Ameen Alamer,1 Ali Ahmed Alghwainem,1 Thabet Abdulaziz Althabit,1 Abdulaziz Alamri,2 Muhammad Ashraf Nazir2 1College of Dentistry Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 2Department of Preventive Dental Sciences, College of Dentistry, Imam Abdulrahman Bin Faisal University, Dammam, Saudi ArabiaCorrespondence: Muhammad Ashraf Nazir Tel +966-543569615Email manazir@iau.edu.saPurpose: Diabetes is a big public health threat in Saudi Arabia. However, there is limited evidence about dental problems, oral hygiene practices, and dental visits among diabetic patients. The study aimed to evaluate self-perceived oral health status and patterns of dental attendance among diabetic patients in the Eastern province of Saudi Arabia.Methodology: This cross-sectional study included 486 diabetic patients (mean age 50.14± 13.59 years) registered with the Saudi Diabetes Society, Saudi Arabia (October-November 2020). The World Health Organization's oral health questionnaire for adults was administered to collect information about oral health status, oral hygiene practices, and dental attendance, in addition to sociodemographic data. Descriptive and analytical statistics were performed.Results: Most participants (66.3%) reported having dental pain or discomfort during the last year. Bad breath (60.50%), tooth cavities (55.10%), difficulty in biting hard food (55.10%), tooth sensitivity (53.30%), and bleeding gums (52.90%) were common oral problems among participants. More than half the sample (55.1%) reported visiting the dental office during the last year. However, pain or trouble with teeth, gums or mouth was the most common (40.5%) reason for the last dental visit. Only 7.8% of participants visited the dentist for a routine dental check-up. Multiple logistic regression analysis showed that Saudi nationality (AOR 2.68, P 0.008), family history of diabetes (AOR 1.88, P 0.022), and having pain during the last year (AOR 4.01, P < 0.001) were the significant factors associated with the last dental visit due to pain.Conclusion: This sample of participants demonstrated a high prevalence of dental problems. Few participants performed routine dental visits and most visits were due to pain. Saudis and patients with family history of diabetes and dental pain were more likely to perform pain related dental visits. Multidisciplinary efforts are needed to develop and implement preventive educational and clinical care models for positive oral and general health outcomes.Keywords: access to oral care, oral health, dental problems, diabetes